Design of integrated circuits for optical communications - Razavi, Behzad (John Wiley & Sons, Inc, 2012)
"The increasing demand for high-speed transport of data has revitalized optical communications, leading to extensive work on high-speed device and circuit design. This book deals with the design of high-speed integrated circuits for optical communication transceivers.Building upon a detailed understanding of optical devices, the book describes the analysis and design of critical building blocks, such as transimpedance and limiting amplifiers, laser drivers, phase-locked loops, oscillators, clock and data recovery circuits, and multiplexers.This second edition of this best selling textbook has been updated to provide information on the latest developments in the field"--